Anna and the Swallow Man - Savit, Gavriel ca. 20./21. Jh (A Borzoi book, 2016)
When her university professor father is sent by the Gestapo to a concentration camp, seven-year-old Anna travels the Polish countryside with the mysterious Swallow Man during World War II.